Impact and safety of adjuvant chemotherapy on pulmonary function in early stage non-small cell lung cancer - Kreuter, Michael; Vansteenkiste, Johan; Herth, Felix; Fischer, Jürgen R.; Eberhardt, Wilfried; Zuna, Ivan; Reinmuth, Niels; Griesinger, Frank; Thomas, Michael (Respiration, 2014)
Background: Pulmonary function may decline after induction chemotherapy and predict perioperative complications in non-small cell lung cancer (NSCLC). The influence of adjuvant chemotherapy is largely indeterminate. Objective: To assess whether adjuvant chemotherapy alters pulmonary function and impacts on treatment-related adverse events. Methods: In a trial on adjuvant chemotherapy (the TREAT trial), 132 patients with R0-resected NSCLC were randomised to 4 cycles of cisplatin-vinorelbine (CVb, n = 65) or cisplatin-pemetrexed (CPx, n = 67). Pulmonary function tests (forced expiratory volume in 1 s, FEV1, forced vital capacity, FVC, total lung capacity, TLC, diffusing capacity for carbon monoxide, DLCO, and blood gas analyses, BGA) were analysed before and 30 days after the last chemotherapy, and changes were calculated (Δ = mean differences). Results: Overall, FVC increased significantly (Δ +290 ml, n = 76; p < 0.0001), while TLC did not change (Δ +220 ml, n = 41; p = 0.174). For CPx, FEV1 increased significantly (Δ +150 ml, n = 47; p = 0.0017), but not for CVb (Δ +30 ml, n = 30). DLCO decreased only for CVb (-8%, n = 6) but not for CPx (-0.39%, n = 17; p = 0.58). BGA did not change (p = 0.99). In a Cox regression analysis, baseline pulmonary function did not influence treatment failure. Conclusions: Adjuvant chemotherapy seems not to result in a decrease of pulmonary function parameters. A significant FVC increase was probably due to ongoing postoperative improvement. Decline of DLCO was noted with CVb but not with CPx. Pulmonary function does not impact on treatment failure.
Published online: October 30, 2013
Gesehen am 29.10.2020